Financial performance of PT. Garuda Indonesia Tbk period 2018-2019 - Muhammad Ichsan Siregar; H. Abdullah Saggaf; Rifani Akbar Sulbahri; Mohammad Aryo Arifin; Muhammad Hidayat; Firmansyah Arifin (Penerbit Goodwood, 2020)
Purpose: This study aims to determine the health level of the financial report of the performance of PT. Garuda Indonesia Tbk with the financial ratios of State-Owned Enterprises for the period 2018-2019. Research methodology: Researchers took the statement of financial position of profit and loss as a tool to assess the soundness of the financial performance of PT. Garuda Indonesia Tbk. Results: In accordance with Decree: KEP-100 / KBU / 2002, as a result, In 2018 PT. Garuda Indonesia Tbk was declared unhealthy with a “CCC” assessment in which the total score obtained from the financial aspect was 21 with a standard assessment of 20 ? TS ? = 30 with the category of assessment “CCC”. Meanwhile in 2019, PT. Garuda Indonesia Tbk was declared unhealthy with a “BB” rating in which the total score obtained from the financial aspect is 45 with a standard assessment of 40 ? TS ? = 50 with the category of rating “BB”. Limitations: Limitations of this research are: this study only took 2 years in the period 2018-2019, the sample taken in this study is a statement of financial position and income. Contribution: This study gives a contribution to policy input from the financial performance of PT. Garuda Indonesia Tbk Keywords: Financial, Performance, Ratios, Financial statements